Deregulation and productivity growth: a study of the Indian commercial banking industry. (21st August 2008) - Zhao, Tianshu; Casu, Barbara; Ferrari, Alessandra
Using a balanced panel data set covering the period of 1992?2004 and employing a Data Envelopment Analysis (DEA)-based Malmquist Total Factor Productivity (TFP) index, this paper aims to examine the impact of regulatory reform on the performance of Indian commercial banks. We also explore whether deregulation has had a different impact on the performance of public, private and foreign banks and whether it affected the risk-taking behaviour of market participants. The empirical results seem to indicate that, after an initial adjustment phase, the Indian banking industry experienced sustained productivity growth, which was driven mainly by technological progress. Banks' ownership structure per se does not seem to matter as much as increased competition in TFP growth. Foreign banks appear to have acted as technological innovators when competition increased, which added to the competitive pressure in the banking market. Finally, our results also indicate an increase in risk-taking behaviour, along with the whole deregulation process.